COMPARISON OF TIMOR-LESTE’S GOOD CORPORATE GOVERNANCE LAW WITH INDONESIA’S ANTI-MONOPOLY LAW TO ENHANCE CORPORATE COMPETITIVENESS - Fernandes, Maria Angelica Araujo; Rahmawan, Dhany; Indiraharti, Novina Sri; Ratnawati, Elfrida (Ridwan Institute, 2025)
The implementation of Good Corporate Governance (GCG) principles in Timor Leste and the implementation of antitrust policies in Indonesia have a significant impact on the competitiveness of companies in both countries. This paper aims to provide a deeper understanding of the comparison between the GCG principles applied in the two countries, both in terms of their implementation challenges and impacts on business competitiveness. The qualitative approach was chosen to understand the phenomenon in depth, identifying the dynamics in the legal and policy contexts in each country. Using the comparative analysis method, the author explores the similarities and differences between the two legal frameworks, as well as analyzes the social and economic impact of these policies on the competition of companies. It is expected that this research can contribute to the development of better economic policies both in the countries and provide insights for other developing countries in optimizing corporate governance and business competition to achieve inclusive and sustainable economic development.